The antibacterial efficacy of calcium hydroxide–iodophors and calcium hydroxide–barium sulfate root canal dressings on Enterococcus faecalis and Porphyromonas gingivalis in vitro - Eric Priyo Prasetyo; Devi Eka Juniarti; Galih Sampoerno; Dian Agustin Wahjuningrum; Ananta Tantri Budi; Dyanita Hasri; Evelyn Tjendronegoro (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: A successful endodontic treatment is inseparable from the right choice of root canal dressing. The right choice of medicaments would result in patient satisfaction. Enterococcus faecalis (E. faecalis) and Porphyromonas gingivalis (P. gingivalis) are usually found in failed root canal treatments. Calcium hydroxide is a gold standard dressing that creates an alkaline environment in the root canal and has a bactericidal effect. Commercially, there are calcium hydroxide dressings with supporting additions, including calcium hydroxide–iodophors (CH–iodophors) and Calcium hydroxide–barium sulfate (CH–barium sulfate). Purpose: This study aimed to compare the antibacterial efficacy between CH–iodophors and CH–barium sulfate root canal dressings on E. faecalis and P. gingivalis. Methods: CH–iodophors and CH–barium sulfate were obtained commercially. E. faecalis and P. gingivalis were obtained from stock culture taken from the root canal of failed endodontic treatment. E. faecalis and P. gingivalis were cultured in Petri dishes, and for each bacterium, 12 wells were made in the media. Six wells were used for the CH–iodophors group, and six wells were used for the CH–barium sulfate group. CH–iodophors and CH–barium sulfate were deployed in the wells in E. faecalis and P. gingivalis cultured media in the Petri dishes. After incubation, the inhibition zone diameters were measured. An independent t-test was used for analysis, and the significance level was set at 5%. Results: There is a significant difference in the antibacterial efficacy of CH–iodophors and that of CH–barium sulfate on E. faecalis and P. gingivalis (p = 0.00001). Conclusion: CH–iodophors have a higher antibacterial efficacy than CH–barium sulfate on both E. faecalis and P. gingivalis.